The Transformation and Application of Virtual and Reality in Creative Teaching: A New Interpretation of the Triadic Ballet - Yi-Wen Ting; Po-Hsien Lin; Chih-Long Lin (MDPI AG, 2023)
Virtual imaging technology has been widely used in entertainment, medicine, engineering and other fields, and the advancement of virtual imaging has also provided new opportunities for art performances and exhibitions. This research uses live dance, screen dance and virtual dance displays to conduct the audience's experience of watching dance performances and compares the three forms. A total of 30 students participated in this research. According to the results of this study, the content of the dance works includes route and trajectory, movements and expressions, costumes, and overall atmosphere; there is no obvious difference under the three viewing conditions, and the spatial performance of dance works is best in live performances. According to the research results, the physical stage performance still has the advantage of space performance, virtual image has the advantage of solving the distance between the audience and the stage, and the screen image is helpful for the performance of the stage color. The results of this study show that the presentation of different technologies can improve the audience's viewing experience of dance, but how to create an impressive spatial experience using the screen image and a virtual environment for a live performance still needs technical improvement.